체질량 지수와 생활습관에 따른 한국 가임 여성의 월경장애 유병률과 변화 추이: 국민건강보험공단 국가건강검진(2009~2016) 자료 활용 - 박소미; 윤태웅; 강대용; 정재원; Park, SoMi; Yoon, Tae Woong; Kang, Dae Ryong; Chung, ChaeWeon (Journal of Korean Academy of Nursing, 2020)
Purpose: This study was performed to identify the prevalence of menstrual disorders in Korean women based on body mass index (BMI) and lifestyle factors, by utilizing the Korean National Health Insurance Database. Methods: A retrospective observational study design was used for the secondary data analysis. Data of women aged 15 to 49 years who were diagnosed with menstrual disorders were extracted from The National Health Insurance Service-National Health Screening Cohort in Korea from 2009 to 2016. The age-standardized prevalence rate of menstrual disorders was calculated using SAS version 9.4, and a Chi-square test and Cochran-Armitage test were performed. Results: In total, 2,219,445 cases were extracted from the database. The prevalence of menstrual disorders significantly increased from 8.6% to 11.6% (Z=135.16, p for trend <.001) over the past eight years. In particular, it was higher in underweight women than in women with normal weight across all years (Z=-4.18~-14.72, p<.001). Moreover, statistically significant differences in the prevalence of menstrual disorders were found to be associated with drinking and smoking in all years and with physical activity levels in part (p<.05~.001). Conclusion: These findings present compelling evidence on the prevalence of menstrual disorders based on a national database. Since the prevalence of menstrual disorders has steadily increased and differs based on BMI and lifestyle factors, educational and clinical interventions are necessary to promote risk awareness and appropriate behavioral changes among Korean women.